Variable mode-mixity during fatigue cycles – crack tip parameters determined from displacement fields measured by digital image correlation (Fracture and Structural Integrity, 2017)
This paper focusses on discussing equivalent stress intensity factors and kink angles after a change of mode-mixity from one cycle to the next and when the mode-mixity changes continuously during the fatigue cycles. Thin-walled tubes with through-wall cracks have been loaded by proportional and non-proportional tension and torsion. In the experimental investigation, the region of fatigue crack growth was observed by applying the digital image correlation technique. Data on the variations of the displacement and strain fields during the cycles were acquired and used to determine mixed-mode variations of stress intensity factors associated with opening modes I, II and III. For each specific specimen the crack path was observed in order to relate its curvature – both kinks and continuously developing warped cracks – with the variations of the displacement field and associated stress intensity factors.
Keywords: Mixed-mode; Fatigue crack growth; Digital image correlation; Crack kinking